Successful immune tolerance induction with low-dose coagulation factor VIII in a patient with hemophilia A from a developing country - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2016)
Inhibitor development is the most frequent and serious complication of the treatment in patients with hemophilia. Immune tolerance induction (ITI) is the only option of treatment for the eradication of factor VIII (FVIII) inhibitor. We would like to present our case with hemophilia whose FVIII inhibitor eradication was done by a low-dose ITI regimen. Our patient has been applied on-demand therapy until 8 years of age. Secondary prophylaxis was began because of having hemophilic arthropathy. A low titer of FVIII inhibitor (4.2 BU/ml) was detected in the fifth month of the prophylaxis. The peak inhibitor titer of patient was 4.6 BU/ml, and there was no decrease in inhibitor titer in the follow-up duration. The low-dose ITI (50 IU/kg, 3 days a week) was started. His inhibitor level was detected negative and the recovery test was ameliorated in the 15th of the ITI therapy. High-dose regimen ITI could not be given particularly in developing countries such as Turkey in view of the high cost of treatment. Patients who had good risk factors might be successfully treated by using low-dose ITI regimen as effective as high-dose ITI regimen. Copyright (C) 2016 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: hemophilia A; immune tolerance induction; inhibitor; INHIBITORS; PREDICTORS